Euro Area Policies : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that the cyclical recovery in the euro area is firming and becoming broad based. Lower energy prices, supportive policies, stronger labor markets and a recovery in credit growth have boosted domestic demand, especially private consumption. The near-term outlook is favorable, with growth of 1.9 percent expected in 2017 and 1.7 percent in 2018. Although headline inflation picked up in the first half of 2017 owing to higher energy prices, core inflation has remained persistently low. The improving near-term outlook is clouded by significant downside risks, especially in the medium and long term, amid thin policy buffers.